Tlingit seal hunter encampment on beach, Yakutat Bay, Alaska, 1899 - Curtis, Edward S., 1868-1952
Small huts on beach, with canoes pulled up on shore. Stretched hides in frames lay on roofs and along sides of huts. Caption on image: Curtis x253a. Copyrighted 1899. E. H. Harriman Caption on mount: Sealer's camp, Yakutat Bay